Implementation of parent-assisted children’s friendship training to address social skills, friendship quality and loneliness in children with autism spectrum disorder - Ong, Sing Yee (2022)
The implications of social skills intervention on peer acceptance, friendship quality, and loneliness among children with autism spectrum disorder (ASD), which remains under-examined, must be thoroughly explored. Although CFT collectively addresses social etiquette and behavioural rules, the percentage of parents with ASD children adopting this strategy is under 25%. The CFT administration and scholars in collectivist countries (Malaysia) relatively disregard parents’ perceptions and experiences. This mixed-method study gathered data with a one-group pre-post-test design through questionnaires pre- and post-intervention. Thirty ASD participants (three females and 27 males) between seven to 12 years old were selected through criterion sampling with inclusion and exclusion criteria. Their subjective views were qualitatively obtained. A semi-structured interview was conducted in a focus group comprising six mothers and two fathers (post-intervention). Concurrently, a 12-session parent-assisted CFT was performed for children and parents. Lessons were practised in multiple settings after each 60 minutesession with parental supervision and guidance. Data analysis with a paired sample t-test revealed statistical significance for social skills based on parent evaluation (t (29) = -4.01, p =.000; d = 0.88). Teacher evaluation [t (29) = -4.12, p = .000; d = 0.85], friendship quality - disengage [t(29) = 4.97, p =.000; d = 0.92], and friendship quality - conflict [t(29) = 4.33, p =.000; d = 0.92] reflected statistically significant differences in pre- to post- parent-assisted CFT. No statistical significance was identified for friendship quality-engage [t (29) = -0.14, p = .891; d = 0.92] and loneliness [t (29) = 0.40, p = .693; d = 0.06]. Parents’ initial CFT experiences were thematically analysed. The parents, who initially hesitated to conduct this training, experienced learning, awareness, and adjustment processes and specific barriers: time commitment, inadequate resources, personal challenges, invited parents’ rejection, and insufficient time and practice for weekly task completion. The social and physical complexities resulting from collectivism were resolved through facilitation, advocating the importance of CFT, and support. Quantitative and qualitative data were reported narratively with contiguous approaches during interpretation and reporting. The ASD children experienced social skills (friendship-building) through parentassisted CFT. These play-based skills, which teach social (friendship-building) and step-by-step CFT techniques with trainers’ and parents’ support, parallel socio-culturist Vygotsky's Zone of Proximal Development (Vygotsky, 1987) and the frameworks underpinning Model of Skills Components Underlying Overt Behaviour (Furman, 1984) and Process-oriented Approach (Taylor & Asher, 1984). The outcomes characterised parents’ experiences and processes during the CFT sessions for stakeholders to aid parental participation and ASD children’s successful friendship development. Parent-assisted CFT implications on improved social skills, disengagement, and conflict behaviour in friendship quality are also empirically supported. Locally, parent-assisted CFT did not influence ASD children’s engagement behaviour, friendship quality, or loneliness reduction. Overall, parent-assisted CFT is a reference for evidence-based intervention to address social competence deficiencies among Malaysian ASD children and their parents’ psychological process, challenges, and adjustments to complete parent-assisted CFT. Stakeholders should also address ASD children’s social abilities and parental engagement in CFT to customise parent-assisted CFTbased programmes, tools, and activities and improve Malaysian ASD children’s life quality.